2017
DOI: 10.1016/j.enzmictec.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Decolourisation of Acid orange 7 in a microbial fuel cell with a laccase-based biocathode: Influence of mitigating pH changes in the cathode chamber

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights of Research1. First Study to observe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…The laccase-based biocathode MFC (lbMFC) produced the maximum open circuit voltage of 250 mV, output voltage of 145 mV (with a 1,000 Ω resistor), power density of 59 mW/m , contributing to the degradation of recalcitrant aromatic compounds [4,5]. In previous studies with the fungal enzyme immobilized on the surface of the cathode, laccase obtained from fungi like Ganodium lucidum strain BCRC 36123, Trametes versicolor, and Pleurotus ostreatus has successfully enhanced the generation of electricity [6][7][8][9][10]. Nevertheless, the enzymes commercially available from the fungal sources and others are quite expensive, as they are produced via a laborious purification process.…”
Section: Introductionmentioning
confidence: 99%
“…The laccase-based biocathode MFC (lbMFC) produced the maximum open circuit voltage of 250 mV, output voltage of 145 mV (with a 1,000 Ω resistor), power density of 59 mW/m , contributing to the degradation of recalcitrant aromatic compounds [4,5]. In previous studies with the fungal enzyme immobilized on the surface of the cathode, laccase obtained from fungi like Ganodium lucidum strain BCRC 36123, Trametes versicolor, and Pleurotus ostreatus has successfully enhanced the generation of electricity [6][7][8][9][10]. Nevertheless, the enzymes commercially available from the fungal sources and others are quite expensive, as they are produced via a laborious purification process.…”
Section: Introductionmentioning
confidence: 99%
“…, acidification at the anode can decrease bacterial activity and affect biofilm stability and performance. Most studies have shown that a pH ranging from 6 to 9 is suitable for growth and operation of biofilms derived from pH‐neutral wastewater . As pH values differ in both chambers of the MFC, this parameter is crucial to the output power generated from MFC.…”
Section: Operating Principle Of Microbial Fuel Cellmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) can be used in the cathode as it can combine with the hydroxide ions and create a carbonate or bicarbonate buffered catholyte system. Some studies have implemented this process and found an increase in power density and cell voltage with a decreased pH imbalance …”
Section: Operating Principle Of Microbial Fuel Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probably for this reason that high enzyme loadings such as 500 U mL −1 to 2000 U mL −1 are used in various dye decolorizing experiments [16,17]. Therefore methods to decrease the enzyme loading and reduce the cost of mediators should be further examined [18]. In this study natural mediators such as syringaldehyde and acetosyringone were studied with relatively low enzyme loadings (300 U L −1 ) with a view to developing a low cost and sustainable laccase-mediator system.…”
Section: Introductionmentioning
confidence: 99%